(untitled) (Balneo and PRM Research Journal, 2024)
Abstract: Serotonin is well known to be involved in the mediation of cognitive processes, but also in the regulation of multiple distinct physiological processes, such as pain. It is also involved in the modulation of nociception of the endogenous analgesic system. Among the monoamine neurotransmitters, serotonin plays an important role in signaling chronic pain, hence the importance of its monitoring in lumbar pain due to degenerative pathology, one of the common cause of this kind of pain. The aim of our study is to evaluate the impact of peloidotherapy on the variation of serum serotonin levels in patients with degenerative low back pain. In our study, conducted in Balneal and Rehabilitation Sanatorium of Techirghiol, we evaluated 130 patients who performed balneal and physical treatments for a period of 2 weeks. The patients were divided into 3 groups: 51 patients were enrolled into the hot mud baths group (HMB), 48 in the cold mud baths (CMB) group and 31 in the control group (CG). Each patient performed physiotherapy treatments which includes electrotherapy, massage and kinetotherapy, patients from HMB group had also hot mud therapy and patients from CMB group had cold mud therapy. Serum serotonin was dosed at admission and at discharge, for each patient, and was determined using ELISA method with kits from Demeditec Diagnostics GmbH for human serotonin. All the data from the study were statistically analized using the SPSS 22.0 program, values were interpreted as mean value and standard deviation, and we used ANOVA and t tests. The statistically significant value considered was p<0.05